Fair Terms of Social Cooperation among Equals - Michael Otsuka (Journal of Practical Ethics)
Rawlsian justice as fairness is neither fundamentally luck egalitarian nor relationally egalitarian. Rather, the most fundamental idea is that of society as a fair system of cooperation. Collective pensions provide a case study which illustrates the fruitfulness of conceiving justice in these latter terms. Those who have recently reached the age of majority do not now know how long they will live in retirement or how well any investments they try to save up for their retirement would fare. From the perspective of the beginning of their working lives, it is therefore rational for each to enter into an agreement with others, who also do not yet know their fates, that, if one turns out to be among the unfortunate whose private pension pots would not have yielded enough for one’s retirement, one will receive much more in retirement, whereas those whose pension pots would have overflowed their retirements will receive somewhat less. These terms are to each person’s expected advantage, which is made possible by a fair sharing of the fruits of social cooperation which arise through the efficiencies reaped by the pooling of the risk of outliving what one could save for one’s retirement on one’s own. It is rational for each to agree to share one another’s fates by pooling risks across both space and time, on fair terms of social cooperation for mutual advantage. Even when collective pensions arise from, and are proportional to, a baseline of unequal income, they can be defended on grounds of reciprocity involving regard for one another as equals.